How „wised up” are we in matters of climate change? - Agg Zoltán; Аґґ З. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2019)
Abstract. In the so-called sociological project we examine the changes related to climate and environment as well as the transformation of values and attitudes and analyze the social contexts of these factors in today's Hungarian society. The environmental problems caused by climate change have already changed the way of thinking both of individuals and social groups, their relation to the environment, and the adverse consequences that enhance the natural environment. It is our assumption that the importance of environmental considerations, their recognition and awareness, and the change of value system are determined by different groups of individuals and communities. It can be influenced by the schooling, township and the age as well. Differences can also be made on the basis of a worldview. Com pared to domestic sociological studies, the novelty of our research is precisely in the study of environmental values by social groups, group awareness, environmental changes and the transformation of value systems in an area where individuals, families and other communities are particularly sensitive to environmental issues.

Szociológiai vizsgálatunk az éghajlati és környezeti változásoknak, valamint az értékrendnek, értékorientációknak és attitűdöknek az átalakulását, ezen tényezők társadalmi összefüggéseit elemzi a mai magyar társadalomban. Az éghajlatváltozás következtében kialakult környezeti problémák megváltoztatják egyének és társadalmi csoportok gondolkodását, környezethez való viszonyát, a kedvezőtlen következmények felértékelik a természeti környezetet. Feltevésünk szerint a környezeti szempontok fontossága, annak felismerése és tudatosulása, az értékrend változása társadalmi csoportonként eltérő, egyének és közösségek kultúrája által meghatározott. Befolyásolhatja az iskolázottság, a települési hovatartozás és az életkor, de valószínűsíthetőek különbségek világnézeti hovatartozás alapján is. A hazai értékszociológiai vizsgálatokhoz képest kutatásunk újszerűségét éppen a környezeti értékek társadalmi rétegenként, csoportonként eltérő tudatosulásának, a környezeti változások és az értékrend átalakulásának vizsgálata adja egy olyan térségben, ahol az egyének, családok és más közösségek környezeti érzékenysége különösen erős.
https://kmf.uz.ua/wp-content/uploads/2021/02/limes-2019_tom-vi_vi-evfolyam.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008405
Keywords: climate change; Balaton; information sources